Age-related decline in the matrix contents and functional properties of human periodontal ligament stem cell sheets. (August 2015) - Wu, Rui-Xin; Bi, Chun-Sheng; Yu, Yang; Zhang, Lin-Lin; Chen, Fa-Ming
Graphical abstract: Abstract: In this study, periodontal ligament (PDL) stem cells (PDLSCs) derived from different-aged donors were used to evaluate the effect of aging on cell sheet formation. The activity of PDLSCs was first determined based on their colony-forming ability, surface markers, proliferative/differentiative potentials, senescence-associated β-galactosidase (SA-βG) staining, and expression of pluripotency-associated transcription factors. The ability of these cells to form sheets, based on their extracellular matrix (ECM) contents and their functional properties necessary for osteogenic differentiation, was evaluated to predict the age-related changes in the regenerative capacity of the cell sheets in their further application. It was found that human PDLSCs could be isolated from the PDL tissue of different-aged subjects. However, the ability of the PDLSCs to proliferate and to undergo osteogenic differentiation and their expression of pluripotency-associated transcription factors displayed age-related decreases. In addition, these cells exhibited an age-related increase in SA-βG expression. Aged cells showed an impaired ability to form functional cell sheets, as determined by morphological observations and Ki-67 immunohistochemistry staining. Based on the production of ECM proteins, such as fibronectin, integrin β1, and collagen type I; alkaline phosphatase (ALP) activity; and the expression of osteogenic genes, such as ALP, Runt-related transcription factor 2, and osteocalcin, cell sheets formed by PDLSCs derived from older donors demonstrated a less potent osteogenic capacity compared to those formed by PDLSCs from younger donors. Our data suggest that the age-associated decline in the matrix contents and osteogenic properties of PDLSC sheets should be taken into account in cell sheet engineering research and clinical periodontal regenerative therapy.